Preparation method of anti-rust magnetic powder core and anti-rust magnetic powder core

By coating the anti-rust agent with organic solvent with ferrosilicon powder and combining insulating agent and passivating agent, a magnetic powder core with long-term anti-rust properties and stable magnetic properties is prepared, which solves the problem of rust easily in the ferrosilicon magnetic powder core and realizes the problem of rust. Environmentally friendly and efficient anti-rust effect.

CN119274954APending Publication Date: 2025-01-07HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444255.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The ferrosilicon magnetic powder core is prone to rust. Existing methods for suppressing rust such as spraying paint and immersion of anti-rust oil have high costs, environmental pollution or poor anti-rust effect, and it is difficult to use in complex environments for a long time.

Method used

The anti-rust agent and organic solvent are mixed with a ferrosilicon powder to coat it, combined with an insulating agent, a passivating agent and a mold release agent, and an anti-rust magnetic powder core is prepared through heat treatment to form a uniform and stable coating layer to improve the anti-rust performance.

Benefits of technology

It realizes long-term rust-proof and environmentally friendly magnetic powder core preparation, ensures magnetic performance, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274954A_ABST
    Figure CN119274954A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-rust magnetic powder core and the anti-rust magnetic powder core, and belongs to the technical field of magnetic materials. The preparation method of the anti-rust magnetic powder core comprises the following steps that 1, an anti-rust agent and a first organic solvent are mixed to prepare a mixed solution, iron-silicon powder and the mixed solution are mixed to obtain mixed powder, the mass of the anti-rust agent accounts for 0.05%-0.4% of the mass of the iron-silicon powder, and the mass of the first organic solvent accounts for 2%-4% of the mass of the iron-silicon powder; step 2, mixing the mixed powder with an insulating agent, a passivating agent and a release agent, and then pressing into a green body; and 3, the blank is subjected to heat treatment, and the anti-rust magnetic powder core is obtained. The antirust magnetic powder core prepared by the method can resist rust for a long time and is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a preparation method of a rust-proof magnetic powder core and the rust-proof magnetic powder core. Background Art

[0002] Iron silicon magnetic powder core is a composite soft magnetic material made by mixing and pressing ferromagnetic powder and insulating medium. Iron silicon magnetic powder core has the characteristics of easy processing and high superposition, and is widely used in electronic components such as inverters, inductors, transformers and chokes, involving many fields such as computers, mobile phones, power supplies, motors, etc. Therefore, iron silicon magnetic powder core needs to have the ability to resist environmental interference so that it can be used normally in more complex working environments.

[0003] Iron silicon magnetic powder core has the disadvantage of being easy to rust. At present, the main methods to inhibit the rust of iron silicon magnetic powder core include spray painting and immersion in anti-rust oil. Spray painting has the disadvantages of high cost and great environmental pollution, and it increases the size of the product and reduces the electromagnetic performance of the product. Immersion in anti-rust oil has the advantages of low cost and no pollution, and it will not change the size of the product, but the anti-rust oil is difficult to enter the interior of the magnetic powder core, the binding force between the anti-rust oil and the magnetic powder is weak, the anti-rust oil is unevenly distributed on the surface of the magnetic powder core, and the magnetic powder core without anti-rust oil is easy to rust when in contact with oxygen and moisture. Therefore, it is necessary to develop a long-term and environmentally friendly anti-rust technology for magnetic powder cores. Summary of the invention

[0004] Therefore, the present invention provides a method for preparing a rust-proof magnetic powder core and a rust-proof magnetic powder core. The rust-proof magnetic powder core prepared by the method of the present invention can prevent rust for a long time and is environmentally friendly.

[0005] To this end, the present invention provides the following technical solutions.

[0006] First, the present invention provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0007] Step 1, mixing a rust inhibitor with a first organic solvent to obtain a mixed solution, and mixing the iron silicon powder with the mixed solution to obtain a mixed powder, wherein the rust inhibitor is 0.05% to 0.4% by mass of the iron silicon powder, and the first organic solvent is 2% to 4% by mass of the iron silicon powder;

[0008] Step 2, mixing the mixed powder with an insulating agent, a passivating agent, and a release agent, and then pressing the mixed powder into a green body;

[0009] Step 3: heat-treating the green body to obtain a rust-proof magnetic powder core.

[0010] In a possible embodiment, the rust inhibitor is 0.05% to 0.2% of the mass of the iron silicon powder.

[0011] In a possible embodiment, the rust inhibitor includes two or more of dinonylnaphthalene sulfonate, 2-mercaptobenzothiazole zinc salt, 5-nitroisophthalic acid, and ammonium benzoate;

[0012] Optionally, the dinonylnaphthalenesulfonate is barium dinonylnaphthalenesulfonate.

[0013] In a possible embodiment, the insulating agent includes one or more of nano-silicon dioxide, nano-alumina, and nano-kaolin;

[0014] In a possible embodiment, the insulating agent is 0.7% to 0.9% of the mass of the iron silicon powder;

[0015] In a possible embodiment, the first organic solvent is selected from one or more of ethanol and methanol.

[0016] In a possible embodiment, the insulating agent includes nano-silicon dioxide and nano-aluminum oxide, and the mass ratio of nano-silicon dioxide to nano-aluminum oxide is (3-1): (1-3); or

[0017] The insulating agent comprises nano silicon dioxide, nano aluminum oxide and nano kaolin, and the mass ratio of the nano silicon dioxide, nano aluminum oxide and nano kaolin is (3-2): (1-3): (1-3).

[0018] In a possible embodiment, the passivating agent includes one or more of phosphoric acid and aluminum dihydrogen phosphate;

[0019] In a possible embodiment, the passivating agent accounts for 0.2% to 0.4% of the mass of the iron silicon powder.

[0020] In a possible embodiment, the release agent includes one or more of zinc stearate and aluminum stearate;

[0021] Optionally, the release agent includes zinc stearate and aluminum stearate, and optionally, the mass ratio of zinc stearate to aluminum stearate is 1:3 to 3:1;

[0022] In a possible embodiment, the release agent accounts for 0.3% to 0.6% of the mass of the iron silicon powder.

[0023] In a possible embodiment, in the step of pressing into a green body in step 2, the pressing pressure is 18-20 T / cm 2 .

[0024] In a possible embodiment, step 3 satisfies at least one of the following conditions:

[0025] (1) The heat treatment temperature is 680-720°C and the holding time is 2-4 hours;

[0026] (2) heat treatment in a nitrogen atmosphere;

[0027] (3) The heating rate of heat treatment is 3-5℃ / min.

[0028] In a possible embodiment, the step of mixing the mixed powder with the insulating agent, the passivating agent, and the releasing agent in step 2 comprises:

[0029] Step 201, mixing the mixed powder with an insulating agent;

[0030] Step 202, mixing the passivating agent with the second organic solvent to prepare a passivating solution, uniformly mixing the product of step 201 with the passivating solution, and then drying;

[0031] Step 203, mixing the product of step 202 with a release agent;

[0032] Optionally, the drying temperature in step 202 is 60° C. to 80° C., and the drying time is 2 to 4 hours;

[0033] Optionally, the second organic solvent in step 202 is 2% to 4% of the mass of the iron silicon powder;

[0034] Optionally, the second organic solvent in step 202 is selected from one or more of ethanol and methanol.

[0035] In a second aspect, the present invention provides a rust-proof magnetic powder core, which is prepared by the above-mentioned preparation method.

[0036] The technical solution of the present invention has the following advantages:

[0037] 1. The preparation method of the rust-proof magnetic powder core of the present invention comprises the following steps: mixing a rust inhibitor with a first organic solvent to obtain a mixed solution, mixing iron silicon powder with the mixed solution to obtain a mixed powder, wherein the rust inhibitor is 0.05% to 0.4% of the mass of the iron silicon powder, and the organic solvent is 2% to 4% of the mass of the iron silicon powder; step 2, mixing the mixed powder with an insulating agent, a passivating agent, and a release agent, and then pressing the mixed powder into a green body; step 3, heat treating the green body to obtain a rust-proof magnetic powder core.

[0038] The present invention dissolves the rust inhibitor in an organic solvent to coat the iron silicon powder, forming a uniform and stable coating layer on the surface of the iron silicon powder to achieve the purpose of long-term rust prevention. The iron silicon powder is first mixed with the rust inhibitor and then mixed with the insulating agent, and the rust inhibitor is directly coated on the surface of the iron silicon powder to further improve the rust prevention effect.

[0039] Moreover, the method of the invention is green and environmentally friendly, and the corresponding preparation process is stable and has good repeatability, and is suitable for mass production.

[0040] 2. The rust inhibitor is 0.05% to 0.2% of the mass of the iron silicon powder. Limiting the amount of the rust inhibitor to this range can improve the rust prevention performance while ensuring the magnetic properties of the rust-proof magnetic powder core. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a graph showing the anti-rust performance test results of the anti-rust magnetic powder core of Example 1;

[0043] Figure 2 This is a graph showing the anti-rust performance test results of the rust-proof magnetic powder core of Example 2;

[0044] Figure 3 This is a graph showing the test results of the rust-proof performance of the rust-proof magnetic powder core of Example 3;

[0045] Figure 4 This is a graph showing the test results of the rust-proof performance of the rust-proof magnetic powder core of Example 4;

[0046] Figure 5 This is a graph showing the anti-rust performance test results of the anti-rust magnetic powder core of Example 5;

[0047] Figure 6 This is a graph showing the test results of the rust-proof performance of the rust-proof magnetic powder core of Example 6;

[0048] Figure 7 This is a graph showing the anti-rust performance test results of the anti-rust magnetic powder core of Example 7;

[0049] Figure 8 This is a graph showing the test results of the rust-proof performance of the rust-proof magnetic powder core of Example 8;

[0050] Fig. 9 This is a graph showing the test results of the rust-proof performance of the rust-proof magnetic powder core of Example 9;

[0051] Fig.10 This is a graph showing the anti-rust performance test results of the anti-rust magnetic powder core of comparative example 1. DETAILED DESCRIPTION

[0052] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0053] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0054] Example 1

[0055] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0056] Step 1, mix the rust inhibitor with ethanol to form a mixed solution, and mix the mixed solution with the iron silicon powder and stir evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate (T705A), 2-thiol benzothiazole zinc salt and ammonium benzoate. The neutral barium dinonylnaphthalene sulfonate is 0.04% of the mass of the iron silicon powder, the 2-thiol benzothiazole zinc salt is 0.07% of the mass of the iron silicon powder, the ammonium benzoate is 0.03% of the mass of the iron silicon powder, and the ethanol dosage is 3% of the mass of the iron silicon powder.

[0057] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano silicon dioxide and nano aluminum oxide, the amount of nano silicon dioxide is 0.6% of the mass of the iron silicon powder, and the amount of nano aluminum oxide is 0.2% of the mass of the iron silicon powder.

[0058] Step 3: Evenly mix phosphoric acid and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 80°C for 2 hours. The amount of phosphoric acid used is 0.2% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0059] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 1:1), mix well, and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0060] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 720°C, and a holding time of 2h. After the holding time is completed, cool it down with the furnace.

[0061] Example 2

[0062] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0063] Step 1, mix the rust inhibitor with ethanol to form a mixed solution, and mix the mixed solution with the iron silicon powder and stir evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate, 5-nitroisophthalic acid and ammonium benzoate. The neutral barium dinonylnaphthalene sulfonate is 0.04% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.06% of the mass of the iron silicon powder, the ammonium benzoate is 0.04% of the mass of the iron silicon powder, and the ethanol is 3% of the mass of the iron silicon powder.

[0064] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano silicon dioxide and nano aluminum oxide, the amount of nano silicon dioxide is 0.2% of the mass of the iron silicon powder, and the amount of nano aluminum oxide is 0.6% of the mass of the iron silicon powder.

[0065] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to form a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 60°C for 4 hours. The amount of phosphoric acid used is 0.2% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate is 0.1% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0066] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 1:3), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0067] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 680°C, and a holding time of 3h. After the holding time is completed, cool it down with the furnace.

[0068] Example 3

[0069] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0070] Step 1, mixing the rust inhibitor with ethanol to form a mixed solution, and mixing the mixed solution with the iron silicon powder and stirring evenly. The rust inhibitor includes 2-mercaptobenzothiazole zinc salt, 5-nitroisophthalic acid and ammonium benzoate. The 2-mercaptobenzothiazole zinc salt is 0.06% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.04% of the mass of the iron silicon powder, the ammonium benzoate is 0.06% of the mass of the iron silicon powder, and the ethanol is 3% of the mass of the iron silicon powder.

[0071] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano-silicon dioxide, nano-alumina and nano-kaolin, the amount of nano-silicon dioxide is 0.3% of the mass of the iron silicon powder, the amount of nano-kaolin is 0.3% of the mass of the iron silicon powder, and the amount of nano-alumina is 0.3% of the mass of the iron silicon powder.

[0072] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 70°C for 3 hours. The amount of phosphoric acid used is 0.1% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate is 0.1% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0073] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 3:1), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0074] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 680°C, and a holding time of 4h. After the holding time is completed, cool it down with the furnace.

[0075] Example 4

[0076] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0077] Step 1, mix the rust inhibitor with ethanol to form a mixed solution, and mix the mixed solution with the iron silicon powder and stir evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate, 2-thiol benzothiazole zinc salt, 5-nitroisophthalic acid and ammonium benzoate. The neutral barium dinonylnaphthalene sulfonate is 0.04% of the mass of the iron silicon powder, the 2-thiol benzothiazole zinc salt is 0.06% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.03% of the mass of the iron silicon powder, the ammonium benzoate is 0.07% of the mass of the iron silicon powder, and the ethanol dosage is 3% of the mass of the iron silicon powder.

[0078] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano-silicon dioxide, nano-alumina and nano-kaolin, wherein the amount of nano-silicon dioxide is 0.3% of the mass of the iron silicon powder, the amount of nano-kaolin is 0.2% of the mass of the iron silicon powder, and the amount of nano-alumina is 0.2% of the mass of the iron silicon powder.

[0079] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 80°C for 2 hours. The amount of phosphoric acid used is 0.2% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate used is 0.2% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0080] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 3:1), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0081] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 700°C, and a holding time of 2h. After the holding time is completed, cool it down with the furnace.

[0082] Example 5

[0083] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0084] Step 1, mix the rust inhibitor with ethanol to form a mixed solution, and mix the mixed solution with the iron silicon powder and stir evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate, 2-thiol benzothiazole zinc salt, 5-nitroisophthalic acid and ammonium benzoate. The neutral barium dinonylnaphthalene sulfonate is 0.06% of the mass of the iron silicon powder, the 2-thiol benzothiazole zinc salt is 0.04% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.04% of the mass of the iron silicon powder, the ammonium benzoate is 0.05% of the mass of the iron silicon powder, and the ethanol dosage is 3% of the mass of the iron silicon powder.

[0085] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano-silicon dioxide, nano-alumina and nano-kaolin, the amount of nano-silicon dioxide is 0.2% of the mass of the iron silicon powder, the amount of nano-kaolin is 0.3% of the mass of the iron silicon powder, and the amount of nano-alumina is 0.3% of the mass of the iron silicon powder.

[0086] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 70°C for 2 hours. The amount of phosphoric acid used is 0.2% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate used is 0.2% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0087] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 1:1), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0088] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 700°C, and a holding time of 4h. After the holding time is completed, cool it down with the furnace.

[0089] Example 6

[0090] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0091] Step 1, mix the rust inhibitor with ethanol to form a mixed solution, and mix the mixed solution with the iron silicon powder and stir evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate, 5-nitroisophthalic acid and ammonium benzoate. The neutral barium dinonylnaphthalene sulfonate is 0.08% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.06% of the mass of the iron silicon powder, the ammonium benzoate is 0.06% of the mass of the iron silicon powder, and the ethanol is 3% of the mass of the iron silicon powder.

[0092] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano-silicon dioxide, nano-alumina and nano-kaolin, the amount of nano-silicon dioxide is 0.4% of the mass of the iron silicon powder, the amount of nano-alumina is 0.2% of the mass of the iron silicon powder, and the amount of nano-kaolin is 0.2% of the mass of the iron silicon powder.

[0093] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 80°C for 2 hours. The amount of phosphoric acid used is 0.15% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate used is 0.15% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0094] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 1:1), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0095] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 720°C, and a holding time of 3h. After the holding time is completed, cool it down with the furnace.

[0096] Example 7

[0097] This embodiment provides a method for preparing a rust-proof magnetic powder core, comprising the following steps:

[0098] Step 1, mixing the rust inhibitor with ethanol to form a mixed solution, and mixing the mixed solution with the iron silicon powder and stirring evenly. The rust inhibitor includes neutral barium dinonylnaphthalene sulfonate, 5-nitroisophthalic acid and 2-thiolbenzothiazole zinc salt. The neutral barium dinonylnaphthalene sulfonate is 0.06% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.07% of the mass of the iron silicon powder, the 2-thiolbenzothiazole zinc salt is 0.04% of the mass of the iron silicon powder, and the ethanol dosage is 3% of the mass of the iron silicon powder.

[0099] Step 2: Evenly mix the powder obtained in step 1 with an insulating agent. The insulating agent is nano-silicon dioxide, nano-alumina and nano-kaolin, wherein the amount of nano-silicon dioxide is 0.3% of the mass of the iron silicon powder, the amount of nano-alumina is 0.2% of the mass of the iron silicon powder, and the amount of nano-kaolin is 0.2% of the mass of the iron silicon powder.

[0100] Step 3: Evenly mix phosphoric acid, aluminum dihydrogen phosphate and ethanol to prepare a passivation solution, evenly mix the powder obtained in step 2 with the passivation solution, and put it into an oven for drying at 80°C for 2 hours. The amount of phosphoric acid used is 0.2% of the mass of the iron silicon powder, the amount of aluminum dihydrogen phosphate used is 0.2% of the mass of the iron silicon powder, and the amount of ethanol used is 3% of the mass of the iron silicon powder.

[0101] Step 4: Pass the powder obtained in step 3 through an 80-mesh sieve, add a release agent (a mixture of zinc stearate and aluminum stearate, mass ratio 1:1), mix well and sieve at 20T / cm 2 The uniformly mixed powder is molded into a 26.9 mm*14.7 mm*11.2 mm ring by pressure, wherein the amount of release agent added is 0.3% of the mass of the iron silicon powder.

[0102] Step 5: Place the ring obtained in step 4 into a nitrogen atmosphere furnace for heat treatment at a heating rate of 4°C / min, a heat treatment temperature of 680°C, and a holding time of 3h. After the holding time is completed, cool it down with the furnace.

[0103] Example 8

[0104] The present embodiment provides a method for preparing a rust-proof magnetic powder core, which is basically the same as Example 7, except that the rust inhibitor of the present embodiment includes neutral barium dinonylnaphthalene sulfonate, 5-nitroisophthalic acid and ammonium benzoate; the neutral barium dinonylnaphthalene sulfonate is 0.2% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.1% of the mass of the iron silicon powder, and the ammonium benzoate is 0.1% of the mass of the iron silicon powder.

[0105] Example 9

[0106] The present embodiment provides a method for preparing a rust-proof magnetic powder core, which is basically the same as Example 3, except that the rust inhibitor of the present embodiment includes 2-thiolbenzothiazole zinc salt, 5-nitroisophthalic acid and ammonium benzoate; the 2-thiolbenzothiazole zinc salt is 0.1% of the mass of the iron silicon powder, the 5-nitroisophthalic acid is 0.1% of the mass of the iron silicon powder, and the ammonium benzoate is 0.2% of the mass of the iron silicon powder.

[0107] Comparative Example 1

[0108] This comparative example is substantially the same as Example 1, except that no rust inhibitor is added and step 1 is not included.

[0109] Test example

[0110] The properties of the rust-proof magnetic powder cores prepared in the embodiments and comparative examples were tested respectively:

[0111] (1) Anti-rust performance test

[0112] Place the sample in a damp heat test chamber and conduct a 336-hour double 85 test: the temperature is set to 85°C, the humidity is set to 85%, and the time is set to 336 hours. After the 336-hour double 85 test, conduct an appearance comparison.

[0113] Test results see Figure 1-Figure 10 As can be seen from the accompanying drawings, the rust-proof magnetic powder core prepared by the method of the present invention has excellent long-term rust-proof performance.

[0114] (2) The magnetic properties of the rust-proof magnetic powder core are tested according to the CEI EN IEC 63300:2024 magnetic powder core electromagnetic properties test method.

[0115] The test results are shown in Table 1.

[0116] Table 1 Performance test data

[0117]

[0118]

[0119] It can be seen from Table 1 that adding 0.05% to 0.2% of the rust inhibitor has little effect on the magnetic properties of the rust-proof magnetic core. When the amount of the rust inhibitor exceeds 0.2%, the loss increases and the magnetic permeability decreases slightly. The preparation method of the present invention and the addition of 0.05% to 0.2% of the rust inhibitor can improve the long-term rust-proof performance while ensuring the magnetic properties of the rust-proof magnetic core.

[0120] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a rust-proof magnetic powder core, characterized in that: The following steps are involved: Step 1, mixing a rust inhibitor with a first organic solvent to obtain a mixed solution, and mixing the iron silicon powder with the mixed solution to obtain a mixed powder, wherein the rust inhibitor is 0.05% to 0.4% by mass of the iron silicon powder, and the first organic solvent is 2% to 4% by mass of the iron silicon powder; Step 2, mixing the mixed powder with an insulating agent, a passivating agent, and a release agent, and then pressing the mixed powder into a green body; Step 3: heat-treating the green body to obtain a rust-proof magnetic powder core.

2. The method for preparing the rust-proof magnetic powder core according to claim 1, characterized in that: The rust inhibitor is 0.05% to 0.2% of the mass of the iron silicon powder.

3. The method for preparing the rust-proof magnetic powder core according to claim 1, characterized in that: At least one of the following conditions is met: (1) The rust inhibitor includes two or more of dinonylnaphthalene sulfonate, 2-mercaptobenzothiazole zinc salt, 5-nitroisophthalic acid, and ammonium benzoate; Optionally, the dinonylnaphthalenesulfonate is barium dinonylnaphthalenesulfonate; (2) The insulating agent includes one or more of nano-silicon dioxide, nano-alumina, and nano-kaolin; (3) The insulating agent is 0.7% to 0.9% of the mass of the iron silicon powder; (4) The first organic solvent is selected from one or more of ethanol and methanol.

4. The method for preparing the rust-proof magnetic powder core according to claim 3, characterized in that: The insulating agent comprises nano silicon dioxide and nano aluminum oxide, and the mass ratio of nano silicon dioxide to nano aluminum oxide is (3-1): (1-3); or The insulating agent comprises nano silicon dioxide, nano aluminum oxide and nano kaolin, and the mass ratio of the nano silicon dioxide, nano aluminum oxide and nano kaolin is (3-2): (1-3): (1-3).

5. The method for preparing the rust-proof magnetic powder core according to any one of claims 1 to 4, characterized in that: At least one of the following conditions is met: (1) The passivating agent includes one or more of phosphoric acid and aluminum dihydrogen phosphate; (2) The passivating agent accounts for 0.2% to 0.4% of the mass of the iron silicon powder.

6. The method for preparing the rust-proof magnetic powder core according to any one of claims 1 to 4, characterized in that: At least one of the following conditions is met: (1) The release agent includes one or more of zinc stearate and aluminum stearate; Optionally, the release agent includes zinc stearate and aluminum stearate, and optionally, the mass ratio of zinc stearate to aluminum stearate is 1:3 to 3:1; (2) The release agent accounts for 0.3% to 0.6% of the mass of the iron silicon powder.

7. The method for preparing the rust-proof magnetic powder core according to any one of claims 1 to 4, characterized in that: In the step of pressing into a green body in step 2, the pressing pressure is 18-20T / cm 2 .

8. The method for preparing the rust-proof magnetic powder core according to any one of claims 1 to 4, characterized in that: The step 3 satisfies at least one of the following conditions: (1) The heat treatment temperature is 680-720°C and the holding time is 2-4 hours; (2) heat treatment in a nitrogen atmosphere; (3) The heating rate of heat treatment is 3-5℃ / min.

9. The method for preparing the rust-proof magnetic powder core according to any one of claims 1 to 4, characterized in that: The step of mixing the mixed powder with the insulating agent, the passivating agent and the releasing agent in step 2 comprises: Step 201, mixing the mixed powder with an insulating agent; Step 202, mixing the passivating agent with the second organic solvent to prepare a passivating solution, uniformly mixing the product of step 201 with the passivating solution, and then drying; Step 203, mixing the product of step 202 with a release agent; Optionally, the drying temperature in step 202 is 60° C. to 80° C., and the drying time is 2 to 4 hours; Optionally, the second organic solvent in step 202 is 2% to 4% of the mass of the iron silicon powder; Optionally, the second organic solvent in step 202 is selected from one or more of ethanol and methanol.

10. A rust-proof magnetic powder core, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.